Hybrid Information Hiding Technique Using Parametric Spline and DFT - Hanaa M; Hala Bahjat Abdul Wahab; Abdul Monem S. Rahma (Engineering and Technology Journal, 2010)
Information hiding is a means to conical and transmitting information usingapparently innocent carrier without depiction any suspicions. This paper presents anew means for information hiding based images by using Hybrid of ParametricSpline and DFT. A set of control points, which represents secret key, are selectsrandomly from the carrier , and a curve pass by the selected control points isimplement using B-Spline. A hiding process for the secret message bits tacksplace on the spectral real part of the intensity pixels where the B-Spline curvepasses by using LSB technique, followed by the IDFT. The paper also presents theinformation hiding features, and techniques for images, and Interpolationtechniques. The Objective fidelity criteria are depicts the improvements inalgorithm with an application example.